Tindak Lanjut Program Kartu Prakerja Skema Normal di Kabupaten Indramayu Prespektif Siyasah Dusturiyah - Fahgita Fildza Azahra; Lutfi Fahrul Rizal; Aji Saptaji (LPPM Universitas Ekasakti Padang, 2024)
The kartu prakerja is one of the policies established by the government based on developing work competencies which is intended for workers/laborers affected by kartu prakerja termination, and/or workers/laborers who need to develop competency skills. The initial implementation of the kartu prakerja Card policy was semi-social assistance during the pandemic in 2020. However, as time went by the economic situation of the workforce in Indonesia returned to stability. So this policy continues to followed, by the program by implementing implementation using a normal scheme, in which there is a role for local governments, in this case the kartu prakerja Service, in providing offline services and training. This research aims to find out how the follow up to the kartu prakerja policy is implemented in Indramayu Regency. By using qualitative descriptive data obtained through oral interviews from sources and the conditions observed. This research was conducted in Indramayu Regency which is one of the districts/cities in West Java Province which was selected to be one of the first 10 Provinces to implement the normal scheme in implementing the kartu prakerja program.